Sex-specific mediating role of insulin resistance and inflammation in the effect of adiposity on blood pressure of prepubertal children - Correia-Costa, Liane; Santos, Ana Cristina; Severo, Milton; Guerra, António; Schaefer, Franz; Afonso, Alberto Caldas; Barros, Henrique; Azevedo, Ana (PLOS ONE, 2015)
Objective To evaluate the association between obesity indices and blood pressure (BP) at 4 years of age, in each sex, and to quantify to which extent this association is mediated by inflammation and insulin resistance (IR). Materials and Methods We studied 1250 4-year-old children selected from the population-based birth cohort Generation XXI. Associations between body mass index (BMI) z-score and waist-to-height ratio (WHtR), office BP, inflammation (high sensitivity C-reactive protein) and IR (HOMA-IR index) were assessed. Path Analysis, a modified multivariate regression approach, was applied to test causal models and quantify direct and indirect effects of predictors of systolic (SBP) and diastolic BP (DBP). Results SBP and DBP increased significantly with BMI and WHtR in both sexes. There was a strong direct association (explaining 74.1-93.2% of the total association) of both measures of adiposity with SBP, in both sexes. This association was additionally indirectly mediated by IR, particularly regarding WHtR (20.5% in girls and 9.4% in boys). Mediation by inflammation did not reach statistical significance in either sex. Regarding DBP, the direct effect of adiposity was strong (>95% for BMI and WHtR in boys) and the mediation by IR was much smaller in boys than in girls. Discussion The direct association between adiposity and BP in healthy 4-year-old children is strong and IR plays an important mediating role. The strength of effects of IR and inflammation suggests sex differences in the complex interplay between BP, adiposity and inflammation.